A Simple Assay for the Detection of Late‐Stage Apoptosis Features in Saccharomyces cerevisiae. Issue 9 (7th September 2022) - Bairwa, Narendra K.; Shoket, Heena; Pandita, Monika; Sharma, Meenu
Abstract: Unicellular eukaryotic organisms such as yeast and protozoa serve as useful models for studying the impact of chemicals on cell physiology, cellular growth, and genome duplication. The yeast Saccharomyces cerevisiae has been widely used to assess apoptosis induced by chemicals due to its genetic tractability, ease of evaluation, and readily available impact assessment tools. Apoptosis in S. cerevisiae is characterized by many features, including increased cell death, loss of membrane integrity, release of caspases, chromatin condensation, and nuclear fragmentation, which are similar to the ones observed in mammalian cells. Current methods of apoptosis assessment typically require specialized equipment and reagents, which limits wide adoption. Here, we describe a rapid, inexpensive, and easy‐to‐perform assay in yeast for the analysis of late‐stage apoptotic features in cells treated with a chemical. We describe a protocol for assessing loss of cell survival and changes in the nucleus. We demonstrate the approach by using acetic acid and hydrogen peroxide as test chemicals. This assay for the study of late‐stage apoptotic features in S. cerevisiae can be performed reliably and rapidly by any laboratory with basic equipment and may be extended for studying apoptosis in similar single‐cell organisms after treatment with toxicological agents. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Culture of Saccharomyces cerevisiae, treatment with acetic acid or hydrogen peroxide, and semi‐quantitative growth assay Basic Protocol 2 : DAPI staining and fluorescence microscopy for the assessment of change in nucleus‐to‐cytoplasm ratio and nuclear integrity